MCITP self-paced training Kit (Exam 70-444) : optimizing and maintaining a database administration solution using Microsoft SQL server 2005 - Thomas, Orin, 1973-; McLean, Ian, 1946- (Redmond, WA : Microsoft Press, 2006)
57